1988
DOI: 10.1063/1.99641
|View full text |Cite
|
Sign up to set email alerts
|

Line shape of the optical dielectric function

Abstract: A systematic study of the optical dielectric function by spectroscopic ellipsometry and electroreflectance has shown that the proper functional form for the Green’s function for an electron-hole pair in GaAs or CdTe is primarily Gaussian, not Lorentzian as is commonly assumed, although it is primarily Lorentzian for Hg1−xCdxTe. The Lorentzian part of the broadening is shown to measure the alloy, impurity, and defect scattering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…effect 32,55,57,[63][64][65] The Lorentzian function has wide wings, which give rise to the excessive absorption below the band gap. Simple Lorentzian broadening, which is frequently used, does not represent accurate approximation of the lifetime broadening.…”
Section: Adjustable Broadening Concept and Modified Critical Pointmentioning
confidence: 99%
See 1 more Smart Citation
“…effect 32,55,57,[63][64][65] The Lorentzian function has wide wings, which give rise to the excessive absorption below the band gap. Simple Lorentzian broadening, which is frequently used, does not represent accurate approximation of the lifetime broadening.…”
Section: Adjustable Broadening Concept and Modified Critical Pointmentioning
confidence: 99%
“…But it should be pointed out that this model gives excellent approximation of both the dielectric function and its first three derivatives. 63 Since broadening is neither pure Gaussian nor pure Lorentzian, an adjustable broadening concept is necessary to deal with this problem. 68 It has been shown that improvement in the agreement with the experimental data can be achieved by replacing the damping constant ⌫ with Eq.…”
Section: Adjustable Broadening Concept and Modified Critical Pointmentioning
confidence: 99%
“…The simultaneous numerical differentiation of both the experimental and model data 14 emphasizes individual CP line shape parameters and greatly reduces parameter correlations, resulting in more stable fits. It has the same sensitivity to alloy composition as E 0 , although its amplitude is significantly smaller.…”
Section: Optimization Of the Model Parametersmentioning
confidence: 99%
“…Nevertheless, even this simple case leads to considerably involved numerical procedures, so that the convolution of the Lorentzian and the Gaussian lineshapes is often replaced by a simple superposition of both lines. Recently, inhomogeneous line broadening has been recognized to significantly influence the dielectric function of semiconductor crystals even below room temperature and several models have been developed to consider Gaussian line broadening in critical point analysis procedures [2,3].…”
Section: Introductionmentioning
confidence: 99%